Baseline characteristics, chromosomal alterations, and treatment affecting prognosis of deletion 17p in newly diagnosed myeloma - Merz, Maximilian; Seckinger, Anja; Hose, Dirk; Mai, Elias K.; Raab, Marc-Steffen; Goldschmidt, Hartmut; Jauch, Anna; Hillengaß, Jens (American journal of hematology, 2016)
Deletion 17p13, del(17p), is associated with poor outcome in myeloma but some patients show long-term survival. With the current study we intended to identify factors impacting outcome of such high risk patients. We analyzed 110 newly diagnosed, symptomatic patients with del(17p) detected by fluorescence in situ hybridization (FISH) in CD138-purified myeloma cells to identify prognostic factors for survival. Age >65 years, ISS III, and elevated LDH negatively impacted survival. Patients with subclonal (10-60% of plasma cells) del(17p) had longer progression-free survival (PFS) than patients with del(17p) in >60% of plasma cells (26 vs. 19 months, P = 0.03). Additional gain of 1q21 was associated with shorter PFS (17 vs. 25 months, P = 0.01). Hyperdiploidy did not ameliorate impact of del(17p), but gain 19q13 predicted longer PFS (30 vs. 18 months, P = 0.01) and overall survival (50 vs. 29 months, P = 0.01). Multivariate analysis in transplant eligible patients (≤65 years) revealed better survival for patients treated with upfront autologous transplantation (hazard ratio, [95% confidence interval]: 0.15 [0.04, 0.58], P = 0.006). Application of maintenance therapy was associated with better survival in transplant-eligible patients (0.30 [0.09, 0.99], P = 0.05). We demonstrate heterogeneous outcome of patients with del(17p) according to baseline characteristics and treatment. 19q13 should be included in routine FISH panel, since gains were associated with better survival. Am. J. Hematol. 91:E473-E477, 2016. © 2016 Wiley Periodicals, Inc.
Gesehen am 28.08.2017